The Problem of the Phonetic Term between Sibawayh, Ibn Jenny and Ibn Sina - AL Tall, Nadeed Omar (Dirasat: Human and Social Sciences, 2023)
Objectives: The paper aims to go beyond what was tackled by research of the phonetic terminology and show the strengths of some terms, which guarantees their persistence. This proves the superiority of one scholar over another in assigning precise terms to specific phonetic concepts. Methods: The inductive, descriptive, analytic and comparative approach was adopted in this study. It relies on collecting as many phoentic terms as possible and classify them in bundles according to shared links of each bundle. These bundles were organized in tables to help readers spot the similarities and differences between them. The terms were then analyzed by showing their meanings and assessing them according to standards common to linguists. Results: The results show that Ibn Jinni was clearly influenced by Sibawayh and that they both are suprior to Ibn Sina in choosing convenient terminologies for the characterstics of letters. Despite Ibin Sina’s issues with terms, his superiority was notable in assiging the terms specific to the places of articulation and speech organs. Conclusions: This study recommends conducting more research in phonetic terminologies and developing a lexicon that help determine the meanings of phonetic terms. This can be achieved with the aid of electronic devices that help researchers discover the precise sound characteristics; thus distinguishing it from other linguistic sounds.